(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
With the exception of a date from the basal fill of the central cist (which is presumed to be redeposited), the dates cluster around the period 1900 to 1500 BC. This supports an early/middle Bronze Age date for the cairn.